O‘ZBEK TALABA YOSHLARI NUTQIDA SLENGLAR VA UNING ADABIY TILGA TA’SIRI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This thesis discusses the definition of the concept of slang, it’s difference from related phenomena, it’s study and use the speech of Uzbek students, and its impact on the literary language.
Keywords: slang, argo, jargon, sociolect, literary language.